2021
DOI: 10.3233/shti210149
|View full text |Cite
|
Sign up to set email alerts
|

Use of Semantic Interoperability to Improve the Urgent Continuity of Care in Danish ERs

Abstract: Reuse of patient data from prehospital electronic health record (EHR) to EHRs in emergency rooms is currently non-existing. In Danish EHRs, access to patient data recorded in prehospital settings is either not available or accessible in a PDF file. The amount of patient and administrative data registered at the prehospital unit is high and includes a rich representation of the accident, the patient and treatment. By applying emphasis framing to the representation of data, information overload can be diminished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…In our review, reported clinical benefits of developing semantic interoperability reflect well the major goals of EHDS regulation. Results in our sample show that, an evident goal driving the development in these studies is the following assumption: through increased access to patient information a better quality and outcomes in care can be achieved [21,23,25,27]. Better communication based on easily accessible data across EHRs is facilitated not only between clinicians and but also between professionals and the patients [26,28,30].…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…In our review, reported clinical benefits of developing semantic interoperability reflect well the major goals of EHDS regulation. Results in our sample show that, an evident goal driving the development in these studies is the following assumption: through increased access to patient information a better quality and outcomes in care can be achieved [21,23,25,27]. Better communication based on easily accessible data across EHRs is facilitated not only between clinicians and but also between professionals and the patients [26,28,30].…”
Section: Discussionmentioning
confidence: 86%
“…It was also documented that semantic interoperability enables data availability from various EHRs and clinical applications specifically for post-marketing research. [21][22][23][24][25][26][27][28][29][30]. In our analysis, semantic development goals were closely coupled with the need to build towards usable and computable data out of heterogeneous medical information that is accessible through various EHRs and databases, e.g., registers.…”
Section: Interoperability Resultsmentioning
confidence: 99%
See 3 more Smart Citations